Expression of the thermogenic nuclear hormone receptor coactivator PGC-1alpha is reduced in the adipose tissue of morbidly obese subjects. - Semple, R; Crowley, VC; Sewter, C; Laudes, M; Christodoulides, C; Considine, R; Vidal-Puig, A; O'Rahilly, S (2004)
Peroxisome proliferator-activated receptor gamma coactivator 1alpha (PGC1alpha) is an accessory protein which can potentiate the transcriptional activation function of many nuclear hormone receptors. Its tissue distribution and physiological studies suggest that its principal in vivo roles are to promote cold-induced thermogenesis, mitochondrial biogenesis, hepatic gluconeogenesis, and fatty acid beta-oxidation. It is expressed in the white adipose tissue of both humans and rodents, and in rodents it has been suggested to mediate in part the leptin-induced conversion of white adipocytes from fat storing to fat oxidising cells. In this study, quantitative real-time PCR has been used in human tissue to demonstrate that (1) PGC1alpha mRNA levels in subcutaneous fat are three-fold lower in morbidly obese than in slim subjects; (2) there are no differences in PGC1alpha mRNA between omental and subcutaneous mature adipocytes; (3) there is a robust induction of PGC1alpha expression during subcutaneous human preadipocyte differentiation ex vivo. Whether low PGC1alpha expression is a prelude to the development of obesity, or a consequence of that obesity, attempts to upregulate endogenous white adipose tissue expression may prove a valuable new avenue to explore in obesity therapy.